2003
DOI: 10.1021/ja0367389
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bond Isomerization in Basic Pancreatic Trypsin Inhibitor:  Multisite Chemical Exchange Quantified by CPMG Relaxation Dispersion and Chemical Shift Modeling

Abstract: Conformational changes occurring on the microsecond-millisecond time scale in basic pancreatic trypsin inhibitor (BPTI) are investigated using nuclear magnetic resonance spectroscopy. The rczz CPMG experiment (Wang, C.; Grey, M. J.; Palmer, A. G. J. Biomol. NMR 2001, 21, 361-366) is used to record (15)N spin relaxation dispersion data, R(ex)(1/tau(cp)), in which 1/tau(cp) is the pulsing rate in the CPMG sequence, at two static magnetic fields, 11.7 and 14.1 T, and three temperatures, 280, 290, and 300 K. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
213
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(225 citation statements)
references
References 85 publications
10
213
1
1
Order By: Relevance
“…The protonation state of ionizable groups corresponds to neutral pH, with the net protein charge neutralized by six chloride ions. A subset of 1,048,349 frames with 0.25-ns spacing, corresponding to a 0.262-ms-long trajectory, was extracted by requiring that the 14-38 disulfide bond is in the experimentally dominant M1 conformation (54). Further details can be found in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…The protonation state of ionizable groups corresponds to neutral pH, with the net protein charge neutralized by six chloride ions. A subset of 1,048,349 frames with 0.25-ns spacing, corresponding to a 0.262-ms-long trajectory, was extracted by requiring that the 14-38 disulfide bond is in the experimentally dominant M1 conformation (54). Further details can be found in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…In very favorable cases a three state model can be used without additional constraints such as addition of ligands or change of temperature (Meinhold & Wright, 2011). There exist a few cases in which three-state models have successfully been applied to proteins undergoing exchange, such as the study by Grey et al (2003) on the multiple states induced by disulfide bond isomerization in the basic pancreatic trypsin inhibitor, and the calculation of structural ensembles of folding intermediates for two Fyn SH3 domain variants reported by Korzhnev et al (2004). It should be noted that the three-state model in Korzhnev et al (2004), was applied under the assumption that (i) the chemical shift differences between exchanging states are temperature-independent, and (ii) the temperature dependence of the rate constants obeys standard transition-state theory (Fersht, 2000).…”
Section: Exchange Modelsmentioning
confidence: 99%
“…In addition, increased transverse 13 C relaxation rates were observed for the C α resonances of Cys14 and Cys38 [9]. Furthermore, it was reported that isomerization of the Cys14 side chain between χ 1 rotamers is faster than the corresponding Cys38 isomerization [10].…”
Section: Introductionmentioning
confidence: 94%
“…Cys14 of BPTI is adjacent to the P1 position, Lys15, and forms a disulfide bond with Cys38, while the corresponding P1 position in BF9 is Asn17 and the corresponding disulfide bond is Cys16-Cys40 based on sequence alignment of BPTI and BF9 [5]. Due to isomerization of the Cys14-Cys38 disulfide bond, two conformational isomers with different chirality were observed in BPTI in the NMR spectra [9,10]. The population of the two isomers is temperature-dependent.…”
Section: Introductionmentioning
confidence: 99%